Current advances in biopharmaceutical informatics: guidelines, impact and challenges in the computational developability assessment of antibody therapeutics. Issue 1 (31st December 2022) - Khetan, Rahul; Curtis, Robin; Deane, Charlotte M.; Hadsund, Johannes Thorling; Kar, Uddipan; Krawczyk, Konrad; Kuroda, Daisuke; Robinson, Sarah A.; Sormanni, Pietro; Tsumoto, Kouhei; Warwicker, Jim; Martin, Andrew C.R.
ABSTRACT: Therapeutic monoclonal antibodies and their derivatives are key components of clinical pipelines in the global biopharmaceutical industry. The availability of large datasets of antibody sequences, structures, and biophysical properties is increasingly enabling the development of predictive models and computational tools for the "developability assessment" of antibody drug candidates. Here, we provide an overview of the antibody informatics tools applicable to the prediction of developability issues such as stability, aggregation, immunogenicity, and chemical degradation. We further evaluate the opportunities and challenges of using biopharmaceutical informatics for drug discovery and optimization. Finally, we discuss the potential of developability guidelines based on in silico metrics that can be used for the assessment of antibody stability and manufacturability.